Whole Genome Sequencing of Chinese White Dolphin (Sousa chinensis) for High-Throughput Screening of Antihypertensive Peptides - Jia, Kuntong (Mar Drugs, 2019)
Chinese white dolphin (Sousa chinensis), also known as the Indo-Pacific humpback dolphin, has been classified as “Vulnerable” on the IUCN Red List of Threatened Species. It is a special cetacean species that lives in tropical and subtropical nearshore waters, with significant differences from other cetaceans. Here, we sequenced and assembled a draft genome of the Chinese white dolphin with a total length of 2.3 Gb and annotation of 18,387 protein-coding genes. Genes from certain expanded families are potentially involved in DNA replication and repairing, suggesting that they may be related to adaptation of this marine mammal to nearshore environments. We also discovered that its historical population had undergone a remarkable bottleneck incident before the Mindel glaciation. In addition, a comparative genomic survey on antihypertensive peptides (AHTPs) among five representative mammals with various residential habitats (such as remarkable differences in exogenous ion concentrations and sea depth) revealed that these small bioactive peptides were highly conserved among these examined mammals, and they had the most abundant hits in collagen subunit proteins, especially for two putative AHTP peptides Gly-Leu-Pro (GLP) and Leu-Gly-Pro (LGP). Our genome assembly will be a valuable resource for further genetic researches on adaptive ecology and conservation biology of cetaceans, and for in-depth investigations into bioactive peptides in aquatic and terrestrial mammals for development of peptide-based drugs to treat various human cardiovascular diseases.